Optimizing artisanal plastic traps for monitoring and managing banana weevils: color, odor, and position - Vélez , Mayra; Garcia-Gaibor, Galo Josue; Guedes, Raul Narciso Carvalho; Rivero-Herrada, Marisol (Revista de Ciencias Agrícolas, 2024)
Banana weevil, Cosmopolites sordidus (Germar), and striped weevil, Metamasius hemipterus (Linnaeus), are pests of global importance in banana cultivation that are traditionally controlled using synthetic insecticides. Plastic traps offer an alternative method to managing these weevils. However, the effectiveness of artisanal traps, considering color, odor, position, and their influence on trapping efficacy, has been largely neglected. Here, we assessed artisanal plastic traps for capturing banana weevils, testing two trap colors (yellow and brown), two positions (horizontal and vertical), and five types of attractants: pineapple; pineapple combined with molasses; pseudostem; pseudostem combined with molasses; and the pheromone Cosmolure in Ecuadorian banana fields. Under controlled conditions, trap color and position did not significantly influence the preference for C. sordidus and M. hemipterus (P<0.05). Field bioassays revealed significant differences in the capture of C. sordidus based on trap position and odor attractants. While trap position did not affect the capture of M. hemipterus, the choice of attractant influenced insect capture rates. Cosmolure was the most effective attractant for capturing banana weevils, whereas pineapple baits attracted the highest number of stripped weevils. Over 10 days, the number of captured insects decreased for both weevils across different attractants. Our findings highlight the potential of artisanal plastic traps as a valuable tool for the integrated pest management (IPM) of C. sordidus and M. hemipterus in banana plantations.